Reconstruction of gluteal deformities: a systematic review and experience of four cases. Issue 5 (3rd September 2017) - Tremp, Mathias; di Summa, Pietro Giovanni; Oranges, Carlo M.; Schaefer, Dirk J.; Kalbermatten, Daniel Felix
Abstract: Background: The reconstruction of gluteal deformities remains a major challenge. The aim of this article is to provide a systematic review of the literature concerned, and to present a case series with representative defects from various zones. Methods: A review of the literature was performed using PubMed, EMBASE, and The Cochrane Library, in accordance with the PRISMA statement. Quality of evidence was rated according to GRADE. Patients with various buttock deformities were included and, depending on the defect, the reconstructive techniques applied consisted of lipoinjection, local fasciocutaneous flap, or pedicled gracilis muscle flap. Complications, patient's pain assessment, impairment in everyday-life activities, aesthetic outcome, objective assessment of sensitivity, and recurrence were considered. Results: A total of 498 records were identified in the literature search. Of those, 12 studies met the PICOS (participants, interventions, comparators, outcomes, and study design) criteria. Overall, 41 patients were analysed, the evidence of which was of low quality. In this study, four patients (three female and one male) with a mean age of 44 ± 15 years were operated on between 2010–2014. The mean operation time was 83 ± 30 minutes. One patient required revision due to persistent seroma and recurrence, and one patient required neurolysis and gracilis denervation due to neuroma and scarring. After a mean follow-up of 40 ± 21 months, the results were functionally and cosmetically satisfactory. Conclusions: Reconstruction of buttock deformities using an integrated approach can lead to a long-lasting, functionally and aesthetically satisfactory result. However, evidence is limited due to the lack of good-quality studies.